Paediatric early warning scores are predictors of adverse outcome in the pre-hospital setting: A national cohort study. (December 2018) - Corfield, A.R.; Silcock, D.; Clerihew, L.; Kelly, P.; Stewart, E.; Staines, H.; Rooney, K.D.
Abstract: Introduction: Physiological deterioration often precedes clinical deterioration as patients develop critical illness. Use of a specific Paediatric Early Warning Score (PEWS), based on basic physiological measurements, may help identify children prior to their clinical deterioration. NHS Scotland has adopted a single national PEWS – PEWS (Scotland). We aim to look at the utility of PEWS (Scotland) in unselected paediatric ambulance patients. Methods: We performed a retrospective cohort of all ambulance patients aged under 16 years conveyed to hospital in Scotland between 2011 and 2015. Patients were matched to their 30 day mortality and ICU admission using data linkage. Results: Full results were available for 21, 202 children and young people (CYP). On multivariate logistic regression, PEWS (Scotland) was an independent predictor of the primary outcome (ICU admission within 48 h or death within 30 days) with an odds ratio of 1.403 (95%CI 1.349–1.460, p < 0.001). Area Under Receiving Operator Curve (AUROC) for aggregated PEWS was 0.797 (95% CI 0.759 to 0.836, p < 0.001). The optimal PEWS using Youlden's Index was 5. Discussion: These data show PEWS (Scotland) to be a useful tool in a pre-hospital setting. A single set of physiological observations undertaken prior to arrival at hospital can identify a group of children at higher risk of an adverse in-hospital outcome. Paediatric care is becoming more specialised and focussed on a smaller number of centres. In this context, use of PEWS (Scotland) in the pre-hospital phase may allow changes to paediatric pre-hospital pathways to improve both admission to ICU and child mortality rates.